Literatur Review: Strategi Mitigasi Konflik Gajah Sumatera-Manusia di Kawasan Konservasi Sumatera - Wan Luzni Rimelahas; Irma Suryani (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
The Sumatran elephant (Elephas maximus sumatranus), classified as Critically Endangered, plays a vital role in maintaining tropical forest ecosystems. However, habitat degradation, fragmentation, and land conversion have escalated human and elephant conflicts in Sumatra. These conflicts cause severe economic losses, crop destruction, and over 200 elephant deaths between 2010 and 2023, mainly from poaching and retaliation. This review aims to examine mitigation strategies implemented in Bukit Barisan Selatan, Way Kambas, and Gunung Leuser National Parks, and to assess their effectiveness and sustainability. Using a literature review method, relevant scientific publications on elephant conflict mitigation were systematically analyzed. Findings indicate that combined structural and non-structural approaches such as sound deterrents, elephant trenches, tame elephant patrols, and community-based units (CRU and ERU) effectively reduce short-term conflicts. Long-term success, however, requires integrated, ecosystem-based strategies emphasizing habitat restoration, corridor connectivity, and adaptive land-use planning. This study highlights the need for humanistic and sustainable mitigation to foster coexistence between humans and Sumatran elephants.